Thermal Performance of De’diba Kulong Ruma Bulongan for Residents Comfort - Icha Anggriani; Ria Wikantari; Baharuddin Hamzah (EPI International Journal of Engineering, 2025)
The Bulungan Stilt House which in local language is called De’diba Kulong Ruma Bulongan has various floor heights of around 30cm, 50cm and 100cm. The difference in stilted floor height is expected to yield different thermal performance that affects occupant comfort. This study aims to: (1) explain the architectural characteristics of De’diba Kulong Ruma Bulongan and the existing conditions of thermal comfort of the occupants, and (2) analyze the effect of the floor height of De’diba Kulong Ruma Bulongan on the thermal comfort based on measurements and occupants perceptions, (3) explain the floor height performance on occupant thermal comfort as a function of climatic and environmental conditions. This research is quantitative, with a survey method using both qualitative and quantitative data. Data were collected through observation, thermal measurements, and distribution of questionnaires to 43 respondents who lived in 9 samples of Bulungan stilt houses. The analysis technique used PMV and PPD through the CBE thermal comfort tools, as well as cross-tabulation of questionnaire data. The results of the analysis of the psychrometric chart and the effective temperature chart at 13:00–14:00 WITA show that the highest average effective temperature in all measured stilt houses is in the range of 25.5-29°C. PMV analysis using the CBE thermal comfort tool shows that houses on stilts are most compliant with Ashrae 55 at a height of 100cm with PMV = 0.02 and PPD feel 5 % of a neutral value with an operating temperature of 25.5 - 27°C. Questionnaire analysis shows the most comfortable thermal reception according to the respondent’s characteristics, namely occupants who are women, elderly (> 54 years old), and those who wear long loose gowns called gamis. The analysis of the occupants' perception shows that the most comfortable thermal reception at the four measurement points of the house on stilts is a house on stilts with a height of subsequently 100, 50, and 30 cm. This study concludes that the floor height affects thermal comfort in which the higher the stilted floor height in the architecture of the De'diba Kulong Ruma Bulongan the more comfortable for the occupants. This study also verifies that thermal comfort is influenced by climatic and environmental conditions.